Assessment of the effects of rehabilitation of hand function using a biometrics device in people after stroke – a randomized controlled trial - Leszczak, Justyna; Pniak, Bogumiła; Gazda, Grzegorz; Guzik, Agnieszka (Frontiers in Neurology, 2025)
PurposeThe aim of the study was to assess the effects of rehabilitation using the Biometrics device on the re-education of hand function in late stroke patients.MethodsThe data were collected from 1 August 2022 to 28 February 2023. The study was conducted among 120 people after stroke, who were randomly assigned to the test (n = 60) or control groups (n = 60). Both groups were provided with a 3-week rehabilitation program for 2 h a day. While the control group received traditional physiotherapy, the test group additionally underwent biofeedback training. Examinations were performed on the first day and the final day of the 3-week intervention program. The primary measurement included assessment of hand grip strength (key, three jaw chuck, tip-to-tip) using an electronic dynamometer and a Biometrics E-link pinchmeter. Secondary outcomes included hand motor function assessment, using the Fugl–Meyer Assessment-Hand Function scale, hand motor dexterity with the Box and Blocks test, hand grip functions according to the Frenchay scale, and functional fitness with the Barthel index.ResultsIn the test group, significant rehabilitation effects were observed for the assessment of grip strength, finger compression strength, manual hand dexterity, grip function and activities of daily living (p < 0.001; p = 0.001), while in the control group results were improved for grip strength and finger compression strength (key and three-jaw chuck) of the right hand (p = 0.012; p = 0.017; p = 0.001) and manual dexterity (p < 0.001), motor abilities and activities of daily living (p < 0.001).ConclusionThe study showed positive effects of hand function rehabilitation in chronic stroke patients in both groups. However, in the test group, which additionally underwent training that stimulated the central nervous system using the biofeedback method with the Biometrics device, better hand and finger grip function as well as hand motor and manual function were noted.Clinical trial registrationhttps://clinicaltrials.gov/, Identifier NCT05486052.